The strange case of Dr. Jekyll and Mr. Hyde - Stevenson, Robert Louis (Helbling readers. Classics)
"When respectable Dr Jekyll starts associating with the mysterious Mr Hyde, his friends become increasingly worried. Who is Hyde and why do all the people he meets dislike him? Stevenson's classic tale of the human capacity for evil is retold with all the tension and gothic drama of the original"